Primary healthcare providers’ views on improving sexual and reproductive healthcare for adolescents in Bolivia, Ecuador, and Nicaragua - Lina Jaruseviciene; Miguel Orozco; Marcia Ibarra; Freddy Cordova Ossio; Bernardo Vega; Nancy Auquilla; Joel Medina; Anna C. Gorter; Peter Decat; Sara De Meyer; Marleen Temmerman; Alexander B. Edmonds; et al. (Taylor & Francis Group, 2013)
Objectives: To elicit the views of primary healthcare providers from Bolivia, Ecuador, and Nicaragua on how adolescent sexual and reproductive health (ASRH) care in their communities can be improved. Methods: Overall, 126 healthcare providers (46 from Bolivia, 39 from Ecuador, and 41 from Nicaragua) took part in this qualitative study. During a series of moderated discussions, they provided written opinions about the accessibility and appropriateness of ASRH services and suggestions for its improvement. The data were analyzed by employing a content analysis methodology. Results: Study participants emphasized managerial issues such as the prioritization of adolescents as a patient group and increased healthcare providers’ awareness about adolescent-friendly approaches. They noted that such an approach needs to be extended beyond primary healthcare centers. Schools, parents, and the community in general should be encouraged to integrate issues related to ASRH in the everyday life of adolescents and become ‘gate-openers’ to ASRH services. To ensure the success of such measures, action at the policy level would be required. For example, decision-makers could call for developing clinical guidelines for this population group and coordinate multisectoral efforts. Conclusions: To improve ASRH services within primary healthcare institutions in three Latin American countries, primary healthcare providers call for focusing on improving the youth-friendliness of health settings. To facilitate this, they suggested engaging with key stakeholders, such as parents, schools, and decision-makers at the policy level.